Accelerated aging and motor control deficits are related to regional deformation of central cerebellar white matter in alcohol use disorder. (1st April 2019) - Zhao, Qingyu; Pfefferbaum, Adolf; Podhajsky, Simon; Pohl, Kilian M.; Sullivan, Edith V.
Abstract: The World Health Organization estimates a 12‐month prevalence rate of 8+% for an alcohol use disorder (AUD) diagnosis in people age 15 years and older in the United States and Europe, presenting significant health risks that have the potential of accelerating age‐related functional decline. According to neuropathological studies, white matter systems of the cerebellum are vulnerable to chronic alcohol dependence. To pursue the effect of AUD on white matter structure and functions in vivo, this study used T1‐weighted, magnetic resonance imaging (MRI) to quantify the total corpus medullare of the cerebellum and a finely grained analysis of its surface in 135 men and women with AUD (mean duration of abstinence, 248 d) and 128 age‐ and sex‐matched control participants; subsets of these participants completed motor testing. We identified an AUD‐related volume deficit and accelerated aging in the total corpus medullare. Novel deformation‐based surface morphometry revealed regional shrinkage of surfaces adjacent to lobules I‐V, lobule IX, and vermian lobule X. In addition, accelerated aging was detected in the regional surface areas adjacent to lobules I‐V, lobule VI, lobule VIIB, and lobules VIII, IX, and X. Sex differences were not identified for any measure. For both volume‐based and surface‐based analyses, poorer performance in gait and balance, manual dexterity, and grip strength were linked to greater regional white matter structural deficits. Our results suggest that local deformation of the corpus medullare has the potential of identifying structurally and functionally segregated networks affected in AUD. Abstract : An AUD‐related volume deficit and accelerated aging was identified in the total corpus medullare. Novel deformation–based surface morphometry revealed regional shrinkage of surfaces and accelerated aging in regional surface areas. For both volume‐based and surface‐based analyses, poorer performance in gait and balance, manual dexterity, and grip strength were linked to greater regional white matter structural deficits.